Maternal Mortality in Henan Province, China: Changes between 1996 and 2009 - You, Fengzhi; Huo, Kaiming; Wang, Ruili; Xu, Dongmei; Deng, Jie; Wei, Ying; Shi, Fenglian; Liu, Hongyang; Cheng, Guomei; Zhang, Zhan; Yang, Ping; Sun, Tao; et al. (PLOS ONE, 2012)
Background Maternal deaths occur mostly in developing countries and the majority of them are preventable. This study analyzes changes in maternal mortality and related causes in Henan Province, China, between 1996 and 2009, in an attempt to provide a reliable basis for introducing effective interventions to reduce the maternal mortality ratio (MMR), part of the fifth Millennium Development Goal. Methods and Findings This population-based maternal mortality survey in Henan Province was carried out from 1996 to 2009. Basic information was obtained from the health care network for women and children and the vital statistics system, from specially trained monitoring personnel in 25 selected monitoring sites and by household survey in each case of maternal death. This data was subsequently reported to the Henan Provincial Maternal and Child Healthcare Hospital. The total MMR in Henan Province declined by 78.4%, from 80.1 per 100 000 live births in 1996 to 17.3 per 100 000 live births in 2009. The decline was more pronounced in rural than in urban areas. The most common causes of maternal death during this period were obstetric hemorrhage (43.8%), pregnancy-induced hypertension (15.8%), amniotic fluid embolism (13.9%) and heart disease (8.0%). The MMR was higher in rural areas with lower income, less education and poorer health care. Conclusion There was a remarkable decrease in the MMR in Henan Province between 1996 and 2009 mainly in the rural areas and MMR due to direct obstetric causes such as obstetric hemorrhage. This study indicates that improving the health care network for women, training of obstetric staff at basic-level units, promoting maternal education, and increasing household income are important interventional strategies to reduce the MMR further.